Do West African thunderstorms predict the intensity of Atlantic hurricanes?. Issue 7 (1st April 2015) - Price, Colin; Reicher, Naama; Yair, Yoav
Abstract Since 85% of all major Atlantic hurricanes originate as thunderstorm clusters in equatorial Africa, we have investigated the connection between these African thunderstorms and the consequent development of these disturbances into tropical storms. We have analyzed Meteosat infrared cloud top temperature data to determine the areal coverage of cold cloud tops over a 6 year period from 2005 to 2010. In addition, hurricane statistics from the same period (intensity, date of generation, location, and maximum winds) were obtained from the National Hurricane Center database. We first show that the areal coverage of cold clouds (with brightness temperatures Tb < −50°C) in tropical Africa is a good indicator of the monthly number of African Easterly Waves (AEWs) leaving the west coast of tropical Africa. Furthermore, the AEWs that develop into tropical storms have a significantly larger area covered by cold cloud tops compared with nondeveloping waves. Finally, we show that on a storm‐by‐storm basis, the cold cloud coverage in West Africa is positively correlated (r = 0.57) with the accumulated cyclone energy of the future tropical cyclones that develop out of these waves.